Acute cardiovascular and inflammatory toxicity induced by inhalation of diesel and biodiesel exhaust particles - Brito, Jôse Mára; Belotti, Luciano; Toledo, Alessandra C.; Antonangelo, Leila; Silva, Flávio S.; Alvim, Débora S.; Andre, Paulo A.; Saldiva, Paulo H. N.; Rivero, Dolores H. R. F. (Oxford University Press (OUP), 2010)
Analysis of fuel emissions is crucial for understanding the pathogenesis of mortality because of air pollution. The objective of this study is to assess cardiovascular and inflammatory toxicity of diesel and biodiesel particles. Mice were exposed to fuels for 1 h. Heart rate (HR), heart rate variability, and blood pressure were obtained before exposure, as well as 30 and 60 min after exposure. After 24 h, bronchoalveolar lavage, blood, and bone marrow were collected to evaluate inflammation. B100 decreased the following emission parameters: mass, black carbon, metals, CO, polycyclic aromatic hydrocarbons, and volatile organic compounds compared with B50 and diesel; root mean square of successive differences in the heart beat interval increased with diesel (p < 0.05) compared with control; low frequency increased with diesel (p < 0.01) and B100 (p < 0.05) compared with control; HR increased with B100 (p < 0.05) compared with control; mean corpuscular volume increased with B100 compared with diesel (p < 0.01), B50, and control (p < 0.001); mean corpuscular hemoglobin concentration decreased with B100 compared with B50 (p < 0.001) and control (p < 0.05); leucocytes increased with B50 compared with diesel (p < 0.05); platelets increased with B100 compared with diesel and control (p < 0.05); reticulocytes increased with B50 compared with diesel, control (p < 0.01), and B100 (p < 0.05); metamyelocytes increased with B50 and B100 compared with diesel (p < 0.05); neutrophils increased with diesel and B50 compared with control (p < 0.05); and macrophages increased with diesel (p < 0.01), B50, and B100 (p < 0.05) compared with control. Biodiesel was more toxic than diesel because it promoted cardiovascular alterations as well as pulmonary and systemic inflammation. © The Author 2010. Published by Oxford University Press on behalf of the Society of Toxicology. All rights reserved. For permissions, please email: journals.permissions@oxfordjournals.org.
Keywords: Biodiesel; Diesel; HRV; Inflammation; Particulate matter; Toxicity